L’utilisation de vidéos Easy French en tant que support pédagogique pour le cours de communication interculturelle - Anisya Windy Wijaya; Mohamad Syaefudin (Universitas Negeri Semarang, 2026)
Studying a foreign language entails an integral exploration of foreign cultures. In the YouTube channel “Easy French”, several videos feature aspects of French culture. For instance, in the video episode titled “What Do the French Eat at Christmas”, the content explains the typical foods consumed by the French during the Christmas holiday. This video can be utilized to illustrate the gastronomy theme in the Communication Interculturelle course. The objective of this research is to describe the suitability of “Easy French” YouTube videos with the course theme and their application in the Communication Interculturelle subject. This study employs a qualitative descriptive approach. The data source for this research comprises 11 videos from the “Easy French” YouTube interculturality playlist. The free conversation and note-taking technique are used to gather data. Subsequently, the data is transcribed onto data cards and analyzed using content analysis techniques. The research results reveal that three videos align with the la géographie theme, two with la gastronomie, and six with les caractères et habitudes. The use of these eleven videos for intercultural communication learning is explained in a semester lesson plan (RPS).